Исследование надежности приборного блока самолета по виброускорениям - Повгородний, В. О. (НТУ "ХПИ", 2006)
In this article are introduced number's index of the fail-safe including vibration accelerations, free frequences and thermal stresses. The problem is soluted by the finite element's method and method of the theory of throw outs. The results for the new device of aircraft, which introduce the pocket of plates with electronical radiotechnical elements
Keywords: виброускорение; логарифмический декремент колебаний; статистическая динамика; конструкции БВП